Professor of the Imperial Military Medical Academy Nikolay Aleksandrovich Velyaminov (1855–1920) (to the 170th anniversary of his birth) - V. M. Lazarev; V. V. Dudka (Вестник хирургии имени И.И. Грекова)
The article presents the main stages of the life and social and scientific activities of Nikolay Aleksandrovich Velyaminov, an outstanding military field surgeon, health care organizer, and head of the Military Medical Academy. Nikolay Aleksandrovich Velyaminov was born on November 15, 1855, in St. Petersburg. After graduating from the Medical Faculty of Moscow University in 1877, he was assigned to the active army and took part in the Russo-Turkish War of 1877–1878 and the military campaign in Central Asia in 1880–1881, where he acquired extensive experience in military field surgery. N. A. Velyaminov constantly combined his military service with clinical and administrative activities in civilian medical institutions. Velyaminov served as the chief physician of the Holy Cross Community of Sisters of Mercy, director of the St. Petersburg Maximilian Hospital, head of the educational department of the Christmas courses for medical assistants and paramedics, and in other medical institutions. N. A. Velyaminov’s military medical career at the court developed rapidly. At the age of 42, he was granted the rank of court surgeon to His Imperial Majesty. N. A. Velyaminov devoted much attention to scientific and journalistic work and from 1885 published a regular surgical journal, which was published for 33 years. In 1989, N. A. Velyaminov defended his dissertation for the degree of Doctor of Medicine, in June 1895, he was appointed extraordinary, and in April 1897, he was approved as an ordinary Professor of the academic surgical clinic of the Military Medical Academy. From 1910 to 1912, N. A. Velyaminov was the head of the Military Medical Academy. As a representative of the Russian Red Cross, he took part in the medical support of Russian troops in all armed conflicts and wars that Russia waged at the beginning of the 20th century. N. A. Velyaminov summarized his experience as a military field surgeon in the manuscript «Essays on the military sanitary affairs of the Russian army in 1914–1917».